Effect of planting time and nitrogen application on the yield and seed quality of T. Aman rice (Oryza sativa L.) - Hussain, ASMI; Hoque, MM; Huda, MN; Hossain, D; Shahjahan, M (Bangladesh Journal of Agricultural Research, 2014)
A field experiment was conducted at the research farm of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur during June 2006 to December 2007 to find out the effect of planting time and nitrogen fertilization on the yield and seed quality of T. Aman rice. BR11 ( Mukta) was transplanted at different dates from 5 July to 19 August at 15 days interval. The rates of N used in the experiment were 80, 100, 120, and 140 kg N/ha,. Plant height, number of tillers/hill, grain yield, and yield components parameters varied significantly due to transplanting of rice at variable dates. The optimum time of planting was found to be 4 August compared to other dates of transplanting. Result indicates that this variety planted in optimum time gave higher yield with high quality of rice seed. In comparison to early and late planting, earlier planting of the variety was better as the late planted crops were severely affected by adverse environmental condition during reproductive phase. The poor grain yield in early or late planting was due to higher percentage of spikelet sterility. The varieties responded positively with increment of N levels upto 120 kg N/ha. The higher number of panicles/m2, lower percentage of unfilled grain, and heavier individual grain contributed to increase grain yield of this verity. It is, therefore, suggested to transplant BR11 rice in the first week of August in Aman season. The application of N of 100 -120 kg/ha with three splits is optimum for achieving higher grain yield and better quality of rice seed. DOI: http://dx.doi.org/10.3329/bjar.v38i4.19660 Bangladesh J. Agril. Res. 38(4): 673-688, December 2013